Lower termite (Coptotermes heimi) gut fibrolytic bacterial consortium: Isolation, phylogenetic characterization, fibre degradation potential and in vitro digestibility. - Pankaj Kumar Kumawat; Srobana Sarkar; Satish Kumar; Artabandhu Sahoo (PLoS ONE)
Lower termites produce wide array of fibrolytic enzymes and serves as prospective microbial enzymes source for enhancing biodegradability of recalcitrant ligno-cellulosic fibrous feeds. The present study was aimed to isolate and characterize anaerobic fibrolytic bacteria from gut of termite Coptotermes heimi for screening promising isolates to improve fiber digestibility in ruminants. A total of 141 isolates were obtained from 97 termite gut samples, and 24 isolates (TM1 to TM24) were selected and characterized as fibrolytic. All isolates were obligatory anaerobes and catalase negative except, TM8, TM9, TM14 and TM22 which were facultative anaerobes and catalase positive. Overall fibrolytic enzyme activity was highest in isolate TM23, TM6 and TM22. Highest FPase activity was observed in isolate TM5 (12.05 U/ml) while, lowest in TM19 (6.41 U/ml). The phylogenetic analysis of the isolates depicted four major families, i.e., Clostridiales, Bacillales, Lactobacillales and Enterobacterales under phyla Firmicutes and Proteobacteria. The in vitro dry matter digestibility of the substrate was increased by 9.4 to 36.0% with the inoculation of isolated bacterial strains. Among the screened isolates, TM6 exhibited highest ability to improve the in vitro dry matter digestibility. The findings of the present study revealed that the fibrolytic bacteria isolated from - termite gut can be used for commercial enzyme production or in rumen biotechnological application for enhancing utilization of fibrous feed in ruminants.